Quantification of Bacterial Metabolic Activities in the Gut by d‐Amino Acid‐Based In Vivo Labeling. Issue 29 (14th May 2020) - Lin, Liyuan; Song, Jia; Du, Yahui; Wu, Qiuyue; Gao, Juan; Song, Yanling; Yang, Chaoyong; Wang, Wei
Abstract: Herein, we propose a metabolic d ‐amino acid‐based labeling and in situ hybridization‐facilitated (MeDabLISH) strategy for the quantitative analysis of the indigenous metabolic status of gut bacteria. The fluorescent d ‐amino acid (FDAA)‐based labeling intensities of bacteria were found to highly correlate with their temporal and steady‐state metabolic status. Then, after taxonomic identification of bacterial genera in the in vivo FDAA‐labeled mouse gut microbiota, by corresponding fluorescence in situ hybridization (FISH) probes, the metabolic activities of different gut bacterial genera are quantified by flow cytometry, using FISH signals to differentiate genera and FDAA signals to indicate their basal metabolic levels. It was found that Gram‐negative genera in the mouse microbiota have stronger metabolic activities during the daytime, and Gram‐positive genera have higher activities at the night. Our strategy will be instrumental in deepening our understanding of the highly complex microbiota. Abstract : Gut sensing : The indigenous metabolic status of mouse gut microbiota is quantified by flow cytometry using the signal from fluorescent d ‐amino acid‐based in vivo labeling as the indicator of bacterial metabolic activities, and signals from fluorescence in situ hybridization to indicate their taxonomic identification.